Evaluación de dos herramientas participativas de diagnóstico comunitario de recursos naturales en la cuencua media del río Nanay, Loreto - Perú, 2020 - Ruiz Ishuiza, Llarlith (2021)
The History of natural resources and the Transect or route are participatory tools used in the community diagnosis of natural resources, but which Both tools had to be subjected to an evaluation to know their effectiveness of application in community work. This research study was developed in three communities located in the middle basin of the Nanay river, Huaturi, San Pablo de Cuyana and Loboyacu, in each community there was the voluntary participation of 8 people, who were older people, made use of natural resources and who were aware of the most important events in the community. In the evaluation of the effectiveness of these tools, two aspects were taken, the effectiveness was based on the tastes and satisfaction of the expectations of the participants, while in the efficiency two indicators were taken into account, the accumulated time and the expenses incurred. The analysis of the results shows that the most effective participatory tool is the Transect or route tool and the most efficient tool is the History of natural resources, with less time and expenses incurred; In other words, the effectiveness of both tools evaluated is divided between effectiveness and efficiency, so it is up to the user to choose the tool that suits them best when they have to carry out future community diagnoses of natural resources.